2006
DOI: 10.1007/s11664-006-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of gold-tin eutectic solder on Cu and Ni substrates

Abstract: The microstructures of the eutectic Au20Sn (wt.%) solder that developed on the Cu and Ni substrates were studied. The Sn/Au/Ni sandwich structure (2.5/3.75/2 m) and the Sn/Au/Ni sandwich structure (1.83/2.74/5.8 m) were deposited on Si wafers first. The overall composition of the Au and the Sn layers in these sandwich structures corresponded to the Au20Sn binary eutectic. The microstructures of the Au20Sn solder on the Cu and Ni substrates could be controlled by using different bonding conditions. When the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…This observation is consistent with the microstructure results of reflowing a Ni/Au/Sn structure at 290°C. 15,16 While the eutectic microstructure and evolution of the plated Au/Sn on Ni after reflow were already investigated in Refs. 15 and 16, our research focus was to bond large Si chips to commercial ceramic packages without using any flux.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with the microstructure results of reflowing a Ni/Au/Sn structure at 290°C. 15,16 While the eutectic microstructure and evolution of the plated Au/Sn on Ni after reflow were already investigated in Refs. 15 and 16, our research focus was to bond large Si chips to commercial ceramic packages without using any flux.…”
Section: Resultsmentioning
confidence: 99%
“…Au is frequently used in electronic products [79][80][81][82][83]. Au bump is used in flexible electronics, and Au finish is important for oxidation prevention.…”
Section: Limited Sn Supply (Au/sn/cu)mentioning
confidence: 99%
“…Eutectic Au-20Sn (in wt.%) solder has been widely used for bonding applications in microelectronic and optoelectronic packages because it can provide relatively low melting point, high strength, low elastic modulus and high thermal conductivity [1][2][3][4][5][6][7][8][9][10][11]. The Au-Sn binary system has a complicated equilibrium phase diagram, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Au-Sn/substrate systems have been extensively studied [8][9][10]16,[18][19][20][21][22][23]. Song et al [16] studied the microstructure of eutectic Au-Sn solder joints on Cu and reported that the microstructure is strongly affected by the addition of Cu from the substrate during reflow.…”
Section: Introductionmentioning
confidence: 99%